Short Report: Choline plasma levels are related to Nrf2 transcriptional expression in chronic kidney disease?. (August 2022) - Mafra, D.; Cardozo, L.; Ribeiro-Alves, M.; Bergman, P.; Shiels, P.G.; Stenvinkel, P.
Summary: Background & Aims: Choline is an amine osmolyte with antioxidant potential. A limited number of studies have implied that choline modulates the nuclear factor-erythroid 2-related factor 2 (Nrf 2) pathway, a major cytoprotectant system. However, there are no data regarding such an interaction in patients with chronic kidney disease (CKD). This cross-sectional pilot study therefore aimed to evaluate the possible relationship between choline plasma levels and transcriptional expression of Nrf2 in patients with CKD on hemodialysis (HD). Methods: This study was performed in 24 HD patients [54 ± 10 years, 14 men, BMI 26.4 ± 4.5 kg/m 2 ]. Choline plasma levels were measured by LC-MS/MS. Nrf2 mRNA expression was measured by real-time quantitative polymerase chain reaction (rt-PCR) in isolated peripheral blood mononuclear cells (PBMC). Results: We used Pearson's correlation (rho) to determine the correlations with Nrf 2 expression and observed a positive correlation between choline plasma levels and Nrf2 (rho = 0.56, P = 0.004). Conclusions: This finding suggests that choline may play a role in Nrf2 expression in CKD.